Modelos Personalizados de Metabolismo de Glucosa para Pacientes Diabéticos Tipo 2 Mediante Algoritmos Evolutivos - Olay Blanco, Ana Alejandra; Quiroz Compeán, Griselda; Torres Treviño, Luis Martín (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
Since type 2 diabetes is a worldwide public health issue, new therapies should be approached. There are recent researches that prove that insulinization therapy can improve the lifestyle of diabetic patients. To have better results with this therapy, it is suggested to use personalized models of the glucose-insulin metabolism of a patient. Therefore, in this paper, the methodology to develop a model based on specific patient data and evolutionary algorithms is shown, as an approach for insulinization therapy.